(untitled) (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
The aims of this study was to determine whether the use of flashcard media can help improve vocabulary mastery of 8th grade students of SMP N 2 Cijambe. The design of this research is experimental research. The sample of this study involved 8th grade students who were divided into two classes 8A with 31 students and 8B with 30 students, with an experimental class of 8A and a non-experimental class of 8B. The data of this study were obtained from two tests, pre-test and post-test.